Pronoun Choises in Bugis: the Road to Encode Politeness - Murni Mahmud (Humaniora, 2011)
This paper discusses the use of pronouns to express Bugis politeness. This is based on the research I conducted in 2005 in two different Bugis communities, one in Awangpone and the other in Parepare. Bugis pronouns such as idi’, ta-, -ki are used by Bugis speakers to express politeness. This use is influenced by factors such as familiarity, differences in age, status, and gender, and the formality and informality of the situation.